2015
DOI: 10.1155/2015/804804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shenque Moxibustion on Behavioral Changes and Brain Oxidative State in Apolipoprotein E-Deficient Mice

Abstract: Purpose. To determine whether moxibustion influences the learning and memory behavior of ApoE−/− male mice, and investigate the mechanism of moxibustion on the alteration of oxidized proteins (glial fibrillary acidic protein, β-amyloid) in hippocampus. Methods. Thirty-three ApoE−/− mice were randomly divided into 3 groups (n = 11/group): moxibustion, sham moxibustion, and no treatment control. Wild-type C57BL/6 mice (n = 13) were used for normal control. Moxibustion was performed with Shenque (RN8) moxibustion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Moxibustion is particularly good at supplementing energy ( qi ), and thus, it has been often applied to patients who experience fatigue or similar conditions [ 25 ]. Modern scientific studies also have shown that moxibustion is effective in alleviating chronic fatigue [ 26 28 ], and some parts of its mechanism have been reported to be related to activation of the vagus nerve [ 26 ], reduction of oxidative damage [ 26 , 27 , 29 ], improvement of inflammation [ 30 ], regulation of the HPA axis [ 10 ], and upregulation of hippocampal progranulin [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moxibustion is particularly good at supplementing energy ( qi ), and thus, it has been often applied to patients who experience fatigue or similar conditions [ 25 ]. Modern scientific studies also have shown that moxibustion is effective in alleviating chronic fatigue [ 26 28 ], and some parts of its mechanism have been reported to be related to activation of the vagus nerve [ 26 ], reduction of oxidative damage [ 26 , 27 , 29 ], improvement of inflammation [ 30 ], regulation of the HPA axis [ 10 ], and upregulation of hippocampal progranulin [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it may improve microcirculation and promote metabolism of the body. Low concentrations of moxa smoke have no noticeable damage to vascular endothelium, while medium concentrations can cause a certain degree of vascular endothelium damage [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive lipid in the plasma will enter the intima of the artery after injury and was accumulated in the artery wall. Deposit in the subintimal space leads to lipid deposition and early atherosclerotic lesions (22). The expression levels of LDL-C, TC and Glu in the model group induced by high-fat diet were significantly higher than those in the normal control group.…”
Section: Discussionmentioning
confidence: 99%